Scanning Violence in the Construction of Subjectivity - Marcela Amador-Calvo (Revista Electrónica Educare)
This paper provides an overview of the construction of subjectivity from an analytical-binding perspective. It explains how the inter-subjectivity of each individual is the result of interplay between inter-subjectivity and trans-subjectivity. It also explains how violence becomes part of the children’s identity when they grow up in a violent environment, at family or school, making them to reproduce the same kind of environment in the future.